Evaluating labor productivity in manufacturing enterprises in Vietnam - Thang, Pham Viet; Tung, Trinh Thanh; Thu, Nguyen Thi Anh; Nam, Vu Quynh (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the factors influencing labor productivity in manufacturing enterprises in Vietnam. The research employs descriptive statistical methods. The results confirm that human resources and the ability to utilize installed technology positively impact labor productivity. These findings align with previous studies. This study provides significant empirical evidence to assist managers and policymakers in formulating appropriate strategies to enhance labor productivity.